2004
DOI: 10.1016/j.rmed.2003.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Relative accuracy of algorithm-based prescription of nasal CPAP in OSA

Abstract: Considerable night-to-night variation means that a one-night titration is not very precise and is subject to random variation. A one-night titration has a similar inaccuracy to that resulting from using an algorithm, based on OSA severity and neck circumference. Setting all patients with OSA at 10 cmH2O is little worse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
50
2
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 11 publications
3
50
2
2
Order By: Relevance
“…Stradling et al identified only neck circumference and OSAHS severity as independent predictors of nasal CPAP titration pressures using unattended auto-CPAP devices. They found that the formula-based approach is as good as one-night titration in estimating CPAP pressure, with similar long-term outcomes for patients [7,23]. The same formula was used by West et al, who reported comparable clinical outcomes of three different methods of determining and delivering the CPAP pressure [24].…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…Stradling et al identified only neck circumference and OSAHS severity as independent predictors of nasal CPAP titration pressures using unattended auto-CPAP devices. They found that the formula-based approach is as good as one-night titration in estimating CPAP pressure, with similar long-term outcomes for patients [7,23]. The same formula was used by West et al, who reported comparable clinical outcomes of three different methods of determining and delivering the CPAP pressure [24].…”
mentioning
confidence: 92%
“…As sleep laboratory availability and expense is an issue of concern, several methods that could shorten long waiting lists and lower costs have been suggested. These are split-night studies [3], auto-CPAP titration [4], home sleep diagnostic studies [5], unattended autotitrating home CPAP studies [6] and more recently CPAP prediction formulas [7][8][9][10].In this issue of Sleep and Breathing, Ozen K. Basoglu and colleagues of the Ege University of Turkey in their paper "Determination of new prediction formula for nasal continuous positive airway pressure in Turkish patients with obstructive sleep apnea syndrome" developed and validated a new prediction formula of optimal CPAP in a Turkish population with OSAS and compared the new formula with two previous formulas designed and validated in Caucasian and Asian populations. The new formula utilizes neck circumference (NC) and oxygen desaturation index (ODI).…”
mentioning
confidence: 99%
See 3 more Smart Citations